The Effect Of Economic Growth, Local Original Income And Equalization Fund On Capital Expenditure (Study On District/City Local Governments In Indonesia) - Tarmidi, Didi; Hendiarto, R. Susanto; Paramudhita, Radea Respati; Putra, Ivan Gumilar Sambas (Owner : Riset dan Jurnal Akuntansi, 2024)
Capital expenditure is a budget expenditure for the acquisition of fixed assets and other assets that benefit more than one accounting period, including expenditures for maintenance costs that maintain or increase useful life, and increase capacity and asset quality. This study aims to examine the effect of Economic Growth, Local Original Revenue, and Balancing Funds on Capital Expenditure in District/City Regional Governments in Indonesia in 2022 both partially and simultaneously. This research uses quantitative methods, using secondary data obtained through the website of the Directorate General of Financial Balance and the website of the Central Statistics Agency. The sampling technique uses the purposive sampling method with a total sample of 218 District/City Regional Governments in Indonesia in 2022. The data analysis method in this study used multiple linear regression analysis. The results of the study show that the variables of Economic Growth, Regional Original Income, and Balancing Funds simultaneously affect Capital Expenditure. Partially, Economic Growth does not affect Capital Expenditure, while Regional Original Revenue and Balancing Fund affect Capital Expenditure.